The Influence of Green MSMEs and Green Finance on Economic Sustainability in Jambi Province with Green Finance as a Mediator - moh Ihsan; Rista Aldilla Syafri; Muhammad Haris Saputra (Cita konsultindo, 2025)
This study aims to examine the impact of green MSMEs on economic sustainability in Jambi Province, the influence of green finance on green MSMEs, and the role of green MSMEs in promoting economic sustainability in Jambi City through green finance. Additionally, it seeks to develop models for Green MSMEs and Green Finance to support a sustainable economy in the region. Employing a Sequential Exploratory Design, this research involved collecting and analyzing quantitative data from 200 MSMEs engaged in environmentally focused businesses. The analysis utilized Smart-PLS to construct the model. The findings indicate that Green MSMEs positively influence Economic Sustainability, Green Finance positively impacts Economic Sustainability, Green MSMEs positively affect Green Finance, and Green Finance serves as an effective mediator in the relationship between Green MSMEs and Economic Sustainability